1990
DOI: 10.1267/ahc.23.487
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical assessment of superoxide dismutase expression in the human endometrium throughout the menstrual cycle.

Abstract: The immunohistochemical distribution of superoxide dismutase (SOD) was examined in the human endometrium throughout the menstrual cycle. Surface and glandular epithelia showed positive staining throughout the menstrual cycle except just prior to the menstruation.Staining activity was more intense in the cytoplasm than that in the nucleus. Specific immunostaining of SOD was demonstrated in sub-and supranuclear vacuoles of glandular epithelia, and intraglandular substances during the early and mid secretory phas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Superoxide anion radicals produced by polymorphonuclear leucocytes cause tissue damage during inflammation (13,25), and the administration of CuZn-SOD has been reported to eliminate or alleviate this damage (1). Recently, we demonstrated the immunohistochemical distribution of CuZn-SOD in the human endometrium, and suggested that CuZn-SOD might play an important role in the local defense mechanisms in the uterus (27). In this study, we demonstrated an intensive CuZn-SOD immunoreactivity in the tubal epithelium of both the ampulla and isthmus portions throughout the menstrual cycle and after menopause.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Superoxide anion radicals produced by polymorphonuclear leucocytes cause tissue damage during inflammation (13,25), and the administration of CuZn-SOD has been reported to eliminate or alleviate this damage (1). Recently, we demonstrated the immunohistochemical distribution of CuZn-SOD in the human endometrium, and suggested that CuZn-SOD might play an important role in the local defense mechanisms in the uterus (27). In this study, we demonstrated an intensive CuZn-SOD immunoreactivity in the tubal epithelium of both the ampulla and isthmus portions throughout the menstrual cycle and after menopause.…”
Section: Discussionsupporting
confidence: 63%
“…Antisera to rhSOD were raised in New Zealand white rabbits. The immunoglobulin fraction was obtained from the antisera, as described previously (27). Localization of the antigens in tissue sections was accomplished by the avidin-biotin-peroxidase complex (ABC) method, described briefly below.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunoglobulin fraction was obtained from the antiserum by protein A Sepharose CL-4B (Pharmacia Fine Chemicals, Uppsala, Sweden) chromatography. Specificity of the immunoglobulin fraction was also confirmed by Ouchterlony's method, as we already reported (32). Immunohistochemical localization of CuZn-SOD was accomplished by the avidin-biotin-peroxidase complex (ABC) method, and 3-amino 9-ethyl carbazol (AEC) was used to visualize the localization of CuZn-SOD.…”
Section: Distribution Of Cuzn-sod In Genital Organsmentioning
confidence: 72%
“…Recently, using a polyclonal antibody produced against recombinant human CuZn-SOD (r-hSOD), we systematically examined the immunohistochemical distribution of CuZn-SOD in the human female (32,33,42) and male genital organs (34). In this review, we discuss the possible roles of CuZn-SOD in the reproductive organs.…”
mentioning
confidence: 99%